Neem combats cowpea pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Cowpea is an important component in several cropping systems prevalent in Africa. It is attacked by numerous insect pests, some of which have proved intractable in research so far. Efforts to control them have included host plant resistance and...